Cognitive Impairments during the Transition to Working at Night and on Subsequent Night Shifts. Issue 4 (August 2019) - McHill, Andrew W.; Wright, Kenneth P.
Demands of modern society force many work operations into the night when the internal circadian timekeeping system is promoting sleep. The combination of disturbed daytime sleep and circadian misalignment, which is common in overnight shift work, decreases cognitive performance, yet how performance may differ across multiple consecutive nights of shift work is not fully understood. Therefore, the primary aim of this study was to use a simulated night-shift protocol to examine the cognitive performance and ratings of sleepiness and clear-headedness across the hours of a typical daytime shift, a first night shift with an afternoon nap and extended wakefulness, and 2 subsequent overnight shifts. We tested the hypothesis that cognitive performance would be worse on the first night shift as compared with the baseline and subsequent nighttime shifts and that performance during nighttime shifts would be reduced as compared with the baseline daytime shift. Fifteen healthy adults (6 men) were studied in the 6-day in-laboratory protocol. Results showed that working during the night increased subjective sleepiness and decreased clear-headedness and performance on the Psychomotor Vigilance Task (i.e., slower median, fastest and slowest reaction times, and increased attentional lapses), Stroop color word task (decreased number of correct responses and slower median reaction time), and calculation addition performance task (decreased number attempted and correct). Furthermore, we observed limited evidence of sleepiness, clear-headedness, or performance adaptation across subsequent nights of simulated night work. Our findings demonstrate that night-shift work, regardless of whether it is the first night shift with a nap and extended wakefulness or subsequent night shifts, decreases performance and clear-headedness as compared with the day shift.